MicroRNA-34a Promotes EMT and Liver Fibrosis in Primary Biliary Cholangitis by Regulating TGF-β1/smad Pathway - Ying Pan; Jing Wang; Lan He; Fengchun Zhang (Journal of Immunology Research)
Background and Aims. Primary biliary cholangitis (PBC) is an autoimmune cholestatic liver disease. We found microRNA-34a (miR-34a), as the downstream gene of p53, was overexpressed in some of fibrogenic diseases. In this study, we sought to explore whether miR-34a plays a role in the fibrosis of PBC. Methods. The peripheral blood of PBC patients and controls was collected to analyze the level of miR-34a. Human intrahepatic biliary epithelial cells (HIBEC) were cultured. The expression of miR-34a was regulated by miR-34a mimics and inhibitor. The biomarkers of epithelium-mesenchymal transition (EMT), fibrogenesis, inflammation, and transforming growth factor- (TGF-) β1/smad pathway were analyzed. Results. We found that miR-34a was overexpressed in the peripheral blood in PBC patients. In vitro, overexpressed miR-34a increased the EMT and fibrogenesis activity of HIBEC. Transforming growth factor-beta type 1 receptor (TβR1), TGF-β1, and p-smad2/3 were upregulated by miR-34a. Inflammatory factors such as IL-6 and IL-17 were also upregulated. Finally, we showed that miR-34a promoted EMT and liver fibrosis in PBC by targeting the TGF-β1/smad pathway antagonist transforming growth factor-beta-induced factor homeobox 2 (TGIF2). Conclusions. Our findings show that miR-34a plays an important role in the EMT and fibrosis of PBC through the TGF-β1/smad pathway by targeting TGIF2. This study suggests that miR-34a may be a new marker of fibrogenesis in PBC. Inhibition of miR-34a may be a promising strategy in treating PBC and improving the prognosis of the disease.